2019
DOI: 10.1249/mss.0000000000002182
|View full text |Cite
|
Sign up to set email alerts
|

Compression Garments Reduce Muscle Movement and Activation during Submaximal Running

Abstract: Purpose The purpose of this study was to investigate the effectiveness of sports compression tights in reducing muscle movement and activation during running. Methods A total of 27 recreationally active males were recruited across two separate studies. For study 1, 13 participants (mean ± SD = 84.1 ± 9.4 kg, 22 ± 3 yr) completed two 4-min treadmill running bouts (2 min at 12 and 15 km·h−1) under two conditions: a no-compression control (CON1) and compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…Their results showed that, while compression shorts did not affect muscle strength acutely, it did reduce the EMG activities and maintained similar power output during repetitive muscle contractions. These results are supported by a recent study from Broatch et al (2019). Thus, we can speculate that reduced motor unit activation might represent a lower metabolic cost at the molecular level.…”
Section: Metabolism Muscle Function and Mechanical Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…Their results showed that, while compression shorts did not affect muscle strength acutely, it did reduce the EMG activities and maintained similar power output during repetitive muscle contractions. These results are supported by a recent study from Broatch et al (2019). Thus, we can speculate that reduced motor unit activation might represent a lower metabolic cost at the molecular level.…”
Section: Metabolism Muscle Function and Mechanical Performancesupporting
confidence: 90%
“…Currently, the relevance of the physiology and biomechanics in fatigue and recovery remains unclear. CGs reduce muscle vibration and activation without affecting performance ( Fu et al, 2012 , 2015 ; Broatch et al, 2019 ). Researchers suggested that, for forms of movements that require frequent and repetitive muscle contractions, reduced muscle activation can improve contraction efficiency and decrease energy loss and muscle fatigue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ehrström et al [ 15 ] showed that wearing high-pressure compression garments (15–20 mmHg) during 40-min treadmill DR (slope: − 15%; intensity: 55% ) likely presented benefits for reducing alterations in the peripheral and central components of neuromuscular fatigue (for KE muscles) immediately after DR, in well-trained trail runners. The beneficial effects of CGs may be explained by an attenuation of soft-tissue vibrations which might improve muscle function [ 238 ], accompanied by lower muscle activity during exercise [ 15 , 239 ]. Ehrström et al [ 15 ] suggested that wearing CGs may exert ‘dynamic immobilization’, reducing soft-tissue oscillation and improving joint stability, and in turn, enhancing neural input [ 240 , 241 ].…”
Section: Adaptation Strategies To Downhill Runningmentioning
confidence: 99%
“…However, since soccer players were not accustomed to DR, this raises the question of the extent of the protective effect conferred by CGs in trained athletes used to running on DR sections. In addition, CGs might contribute to enhanced post-exercise muscle recovery [ 15 , 239 ]. A greater mechanical protective effect was also observed during the recovery period in KE compared to PF muscles only when athletes wore CGs during DR.…”
Section: Adaptation Strategies To Downhill Runningmentioning
confidence: 99%